The Utilization of Ultrasound-Guided Regional Nerve Blocks in Anesthetic Management for Fracture Surgery - Yi R; Li Z; Yang X; Huang T; Liu H; Zhang J (Journal of Pain Research)
Ruofan Yi,1 Zeng Li,1 Xingjun Yang,2 Ting Huang,1 Hongjun Liu,1 Jun Zhang2 1Department of Anesthesiology, The 955th Hospital of Chinese People’s Liberation Army, Tibet, 854000, People’s Republic of China; 2Department of General Surgery, The 955th Hospital of Chinese People’s Liberation Army, Tibet, 854000, People’s Republic of ChinaCorrespondence: Jun Zhang, Department of General Surgery, The 955th Hospital of Chinese People’s Liberation Army, No. 52, Gadong Street, Karuo District, Chamdo, Tibet, 854000, People’s Republic of China, Tel +86 0895 4820722, Email junzhangyz@outlook.com Hongjun Liu Department of Anesthesiology, The 955th Hospital of Chinese People’s Liberation Army, No. 52, Gadong Street, Karuo District, Chamdo, Tibet, 854000, People’s Republic of China, Tel +86 0895-4820775, Email hongjunliumzk@outlook.comAbstract: Fracture surgeries are frequently accompanied by severe pain, necessitating efficacious pain management strategies to enhance postoperative recovery. Nerve block techniques, which are critical in mitigating pain, involve the targeted administration of local anesthetics to disrupt nerve signal transmission, thereby achieving significant analgesia. Traditionally, these techniques rely on anatomical landmarks and the clinician’s expertise, which can introduce variability and potential risks. The adoption of ultrasound-guided nerve blocks has increased, facilitated by advancements in imaging technology. This approach enables precise placement of anesthetics through real-time visualization of neural structures and adjacent tissues, significantly improving the accuracy and safety of the procedure. This review summarizes recent advancements in the application of ultrasound-guided nerve block techniques in fracture surgeries, particularly for rib, upper limb, thoracic, lumbar, and hip fractures. By precisely placing local anesthetics, these techniques not only improve the safety and efficiency of surgeries but also significantly reduce postoperative pain and recovery time. The widespread application of ultrasound-guided nerve blocks offers an efficient and low-side-effect anesthesia management strategy, enhancing post-surgical patient experience and recovery quality.Keywords: ultrasound-guided nerve blocks, fracture surgery, postoperative pain management, anesthetic precision and safety